Mechanical factors associated with the development of high ball velocity during an instep soccer kick - de Witt, J. K.; Hinrichs, R. N. (Sports Biomechanics, 2012)
The purpose of this study was to determine whether joint velocities and segmental angular velocities are significantly correlated with ball velocity during an instep soccer kick. We developed a deterministic model that related ball velocity to kicking leg and pelvis motion from the initiation of downswing until impact. Three-dimensional videography was used to collect data from 16 experienced male soccer players (age = 24.8 ± 5.5 years; height = 1.80 ± 0.07 m; mass = 76.73 ± 8.31 kg) while kicking a stationary soccer ball into a goal 12 m away with their right foot with maximal effort. We found that impact velocities of the foot center of mass (CM), the impact velocity of the foot CM relative to the knee, peak velocity of the knee relative to the hip, and the peak angular thigh velocity were significantly correlated with ball velocity. These data suggest that linear and angular velocities at and prior to impact are critical to developing high ball velocity. Since events prior to impact are critical for kick success, coordination and summation of speeds throughout the kicking motion are important factors. Segmental coordination that occurs during a maximal effort kick is critical for completing a successful kick.